Evaluasi pelaksanaan TQM untuk peningkatan kualitas pembelajaran di STAI Darussalam Kunir: Perspektif mahasiswa dan dosen - Aminuddin, Aminuddin; Qothrun Nada Rahmah, Alisa; Syihabuddin, Syihabuddin; Asep Kuswara, Mochammad (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2024)
This study aims to evaluate the implementation of Total Quality Management (TQM) at STAI Darussalam Kunir and its impact on learning quality. Using a descriptive qualitative approach, the study involved in-depth interviews, observations, and documentation collection from students and lecturers. The results show that the implementation of TQM has succeeded in creating a better learning environment, increasing student involvement in decision-making, and strengthening the relationship between higher education and the professional world. The implementation of TQM at STAI Darussalam Kunir focuses on meeting the needs of students and the world of work, with relevant curriculum adjustments and supporting programs such as Community Service (KKN) and Student Activity Units (UKM). Through this approach, educational institutions not only improve academic quality, but also equip students with practical skills needed in the labor market. The findings of this study confirm that TQM is an effective strategy to improve the quality of education at STAI Darussalam Kunir. By involving all elements of the organization in the management process, TQM helps create a culture of continuous evaluation that supports the development of educational quality. Therefore, the institution can be more competitive and responsive to global challenges in biology.